DOES THE PROMOTION OF ADMINISTRATIVE JUSTICE ACT APPLY TO DISMISSALS IN THE PUBLIC SECTOR?* Transnett Lttd v Chiirwa ((2007)) 11 BLLR 10 SCA - JP Partington; JA van der Walt (Obiter, 2022)
The Supreme Court of Appeal (hereinafter “the SCA”) was recently tasked with resolving the elusive answer to an unsettled question: may employees in the public service challenge dismissals and other forms of alleged unlawful practices in the High Court as infringements of their right to lawful, rational and procedurally fair administrative action? The High Court and the Labour Court have been divided on the issue to such an extent that neither forum has managed to follow a consistent approach. The uncertainty has arisen, in essence, from two irreconcilable bases: the first, that dismissals and other employment practices in the public sector do not constitute administrative action, and so cannot be subjected to scrutiny under the common law, the PAJA or the Constitution; the second, that public sector employees have always been regarded as administrative law subjects under the common law, and as the PAJA does not expressly alter the position, they retain the protection. Amid this legal setting of uncertainty emerged Ms Chirwa. She was dismissed for alleged incompetence following an enquiry in which she refused to participate as she was adamant that the presiding manager was biased or could reasonably be seen to be biased against her. She challenged her dismissal in the High Court as an infringement of her right to lawful, reasonable and procedurally fair administrative action in terms of the PAJA, alternatively the Constitution. (S 33(1) of the Constitution reads: “Everyone has the right to administrative action that is lawful, reasonable and procedurally fair.”) The court agreed with Ms Chirwa’s contentions, declared her dismissal a nullity, and reinstated her with retrospective effect. (Brassey AJ found that Transnet had breached the audi alteram partem rule, a principle of natural justice applicable to pubic sector dismissals. This case note does not offer a critique of the court a quo’s decision.) On appeal, Transnet contended that Ms Chirwa’s dispute was one over which the Labour Court had exclusive jurisdiction in terms of section 157(1) of the LRA, (s 157(1) of the LRA which reads: “Subject to the Constitution and section 173, and except where this Act provides otherwise, the Labour Court has exclusive jurisdiction in respect of all matters that elsewhere in terms of this Act or in terms of any other law are to be determined by the Labour Court.”); alternatively, that her dismissal did not constitute administrative action as defined in section 1 of the PAJA. Put simply, the issue on appeal was whether Ms Chirwa had an administrative justice cause of action justiciable in the High Court. Of the five judges who heard the appeal, three held that the High Court could not assist her. On the face of it, Chirwa therefore appears to have resolved the jurisdictional dispute in favour of the exclusive jurisdiction of the Labour Court in employment disputes. However, scratching the surface of the judgment, the worth of its appearance quickly fades. This case note offers a critique and attempts to determine the real worth of Chirwa, a judgment by what, as will be explained, was actually a divided bench of the SCA.